2020
DOI: 10.1021/acs.chemrev.0c00015
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Factors Influencing the Printability of Hydrogel-based Extrusion Bioinks

Abstract: Bioprinting researchers agree that “printability” is a key characteristic for bioink development, but neither the meaning of the term nor the best way to experimentally measure it has been established. Furthermore, little is known with respect to the underlying mechanisms which determine a bioink’s printability. A thorough understanding of these mechanisms is key to the intentional design of new bioinks. For the purposes of this review, the domain of printability is defined as the bioink requirements which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 445 publications
2
94
0
Order By: Relevance
“…In these last fields, hydrogels of different origins are usually extruded from a needle or nozzle, thus forming fibers of variable size (from milli to micro) with the designed geometry 19 . The capability of a material to be extruded in self-standing fibers with dimensions suitable for a specific application is defined "printability" [20][21][22] . The development of new inks for 3D-printing is a complex challenge as different parameters, such the polymer type, concentration and degree of crosslinking, require efforts and time to be optimized in terms of printability 19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…In these last fields, hydrogels of different origins are usually extruded from a needle or nozzle, thus forming fibers of variable size (from milli to micro) with the designed geometry 19 . The capability of a material to be extruded in self-standing fibers with dimensions suitable for a specific application is defined "printability" [20][21][22] . The development of new inks for 3D-printing is a complex challenge as different parameters, such the polymer type, concentration and degree of crosslinking, require efforts and time to be optimized in terms of printability 19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are crosslinked polymer networks swollen by water with content typically higher than 90% [18][19][20][21][22][23] . As mostly aqueous materials, hydrogels have shown promises in various bio-related fields due to their high water content and softness which provides excellent compatibility with biological tissues 24,25 . These two characteristics, however, limit their potential for wider applications in particular for non-bio-related manufacturing.…”
Section: Dmentioning
confidence: 99%
“…Chen et al reported on a photocurable piezoelectric ink suitable for additive manufacturing [193]. In the bioprinting research, additional factors must be investigated, as the optimal printing parameters for manufacturing a 3D architecture could not be suitable for cell survival, thus pointing out that the rheological properties of the bioink are fundamental [194]. Hydrogel composition together with printing parameters strongly affect printability in terms of desired shape resolution, as demonstrated using pure alginate or alginate with gelatin and methyl-cellulose [195].…”
Section: D (Bio-)printing: Cutting Edge Applications and Future Persmentioning
confidence: 99%